Hazing Violence: Practices of Domination and Coercion in Hazing in Portugal. Issue 11 (June 2018) - Fávero, Marisalva; Pinto, Sofia; Ferreira, Fátima; Machado, Francisco; Del Campo, Amaia
The moment of entry into university marks an important transition for students in Portugal. Their new situation requires an update and a new personal, academic, and social contextualization and, in this new universe, hazing plays a significant role. This study aimed to understand the phenomenon of hazing in Portugal, analyzing, specifically, the violent behaviors that can occur in this context. To this effect, we have developed the Questionnaire for the Assessment of Experience in Hazing (QAVPA)—a questionnaire that allows the analysis of Portuguese students' hazing experiences and situations of violence. This questionnaire was applied to a sample consisting of 586 university students and ex-students who participated in hazing, 393 (67.1%) women and 193 (32.9%) men, with ages between 18 and 47 years ( M = 23.27, SD = 4.24). From the gathered data, 77.8% were victims of violence in hazing rituals, 86.9% witnessed violent practices, and 39.8% admitted having had violent behaviors toward new students. It was also found that variables such as having been a victim of this type of violence, sex, type of education, and hierarchy level are associated with the perpetration of violence in this context.